Systematic Review of the Link Between Oxford MEST-C Classification and Complement Activation in IgA Nephropathy - Gabriel Ștefan; Eric Alamartine; Christophe Mariat; Nicolas Maillard (Kidney International Reports)
Introduction: IgA nephropathy's (IgAN’s) MEST-C classification relationship with complement activation is still not fully understood because of limited and conflicting evidence. Our study aimed to delineate this relationship through a systematic review. Methods: We adhered to the Preferred Reporting Items for Systematic Review and Meta-analysis guidelines and conducted a systematic review, utilizing databases like MEDLINE (PubMed), Embase, Scopus, and Cochrane from January 2016 (year of updated MEST-C classification) to January 2023. We specifically selected studies that employed established methods to evaluate complement activation and the MEST-C classification. Results: A total of 34 studies with 10,082 patients were included. Among these, 7 studies focused on the pediatric population (500 patients), and 22 studies involved 8128 patients from Asian populations. C4d, C3, C5b9, MBL, C4, and factor H-related protein 5 (FHR5) were the most frequently studied complement proteins in relation to the MEST-C classification. Complement activation assessment was primarily conducted using immunofluorescence and immunohistochemistry on kidney biopsy specimens. All complement proteins investigated showed associations with the C1-2 class. Notably, FB, FH, MASP1/3, MASP2, C5a, and C5b9 from the alternative, lectin, and terminal pathways were uniquely present in the C1-2 class. Whereas C3, FHR5, C4, and C4d were associated with all the MEST-C classes. Conclusion: We found evidence supporting the involvement of alternative and lectin complement pathways across all MEST-C classes. All examined complement factors were associated with the C1-2 class, emphasizing the critical role of complement activation, possibly at the endothelial surface. These findings may guide the development of personalized treatment strategies targeting complement pathways in relation to the MEST-C lesions.